2010
DOI: 10.1089/thy.2009.0045
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Contrast-Enhanced Ultrasound for Evaluation of Thyroid Nodules

Abstract: Contrast-enhanced US enhancement patterns were different in benign and malignant lesions. Ring enhancement was predictive of benign lesions, whereas heterogeneous enhancement was helpful for detecting malignant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(141 citation statements)
references
References 12 publications
6
127
0
5
Order By: Relevance
“…According to our data, the most reliable symptom of benignity was the rim-like enhancement presenting 94% sensitivity, 61% specificity, and 77% accuracy. In accordance with our results, also in studies by Zhang et al (2010), Cantisani et al (2013) and Ma et al (2014) rim-like enhancement is specific to benign nodules. Results yielded by Zhang et al (2010) showed 94.1% specificity, 83.0% sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to our data, the most reliable symptom of benignity was the rim-like enhancement presenting 94% sensitivity, 61% specificity, and 77% accuracy. In accordance with our results, also in studies by Zhang et al (2010), Cantisani et al (2013) and Ma et al (2014) rim-like enhancement is specific to benign nodules. Results yielded by Zhang et al (2010) showed 94.1% specificity, 83.0% sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…The results are ambiguous and sometimes contradictory. The diagnostic value of CEUS has been analysed in only very few studies (Ferrari et al, 2008;Zhang et al, 2010;Nemec et al, 2012;Cantisani et al, 2013;Giusti et al, 2013;Deng et al, 2014;Ma et al, 2014), yielding variable results; the sensitivity varies between 68-100% and specificity -between 67-594%.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement features of lesion on CEUS included: i) Margin enhancement, defined as clear or unclear based on the clarity of the margin between the lesion and peripheral tissue; ii) shape enhancement, classified as regular or irregular based on the shapes observed following contrast agent injection; iii) area enhancement, defined as <50 or ≥50% based on the area of the enhancement part/the lesion section at the peak enhancement; iv) enhancement degree, characterized as low, equal or high intensity when compared with the surrounding thyroid parenchyma; and v) type of enhancement, including homogeneous (relative homogeneous diffuse enhancement in lesions), heterogeneous (diffuse enhancement presenting inhomogeneous or regional microvesicle distribution) and ring enhancement (ring structure, such as round, oval or oblate spheroid). In CEUS, lesions that showed inhomogeneous and low enhancement were considered as diagnostic criteria for malignant nodules (29,30). Elasticity was classified in five different patterns on RTE scans, as described previously (31,32).…”
Section: Subjectsmentioning
confidence: 99%
“…Up to 50% of medullary thyroid carcinoma demonstrate bright echogenic foci; indicative of deposits of calcium surrounded by amyloid. Cystic change is unusual for medullary thyroid carcinoma (134,135).…”
Section: Cytologic Diagnosis Of Medullary Thyroid Carcinomamentioning
confidence: 99%